Research on Inventory Control and Pricing Decisions in the Supply Chain of Fresh Agricultural Products Under the Advertisement Delay Effect - Jiang Yong-Chang; Cao Jia-Xu; Zhu He-Jie (IEEE Access)
The transportation and preservation of fresh products are critical determinants of consumer purchasing behavior and market demand. Due to the perishable nature and short lifecycle of these products, delays in sales can lead to challenges such as diminished resale or reprocessing opportunities and significant losses in inventory value. This study investigates a fresh agricultural product supply chain consisting of suppliers, retailers, and third-party logistics (TPL) service providers. Employing optimal control theory and Stackelberg game theory, it examines the effects of advertising delays on inventory management, product reputation, and supply chain performance. The research identifies optimal equilibrium strategies, inventory trajectories, and profit outcomes across different decision-making scenarios. The key findings are as follows: (1) Advertising delays are positively associated with the retailer’s advertising investment level, while the retail price, TPL service quality, and supplier’s preservation investment remain unaffected by delay duration. (2) Prolonged advertising delays lead to extended replenishment cycles for fresh agricultural products. Implementing joint inventory management and sharing advertising costs can alleviate inventory overstock resulting from these delays. (3) Advertising delays weaken or nullify the effectiveness of cost-sharing coordination mechanisms, reflected in reduced cost-sharing proportions and diminished total supply chain profits. This study provides valuable insights into optimizing decision-making and coordination in fresh product supply chains, addressing the challenges posed by advertising delays.